Purification and characterization of peroxidases from garden cress sprouts and their roles in lignification and removal of phenol and p‐chlorophenol. Issue 1 (2nd November 2020) - Abdel‐Aty, Azza M.; Salama, Walaa H.; El‐Badry, Mohamed O.; Salah, Hala A.; Barakat, Amal Z.; Fahmy, Afaf S.; Mohamed, Saleh A.
Abstract: The study aims to evaluate the relation between peroxidases of day‐6 garden cress sprouts and phenolic compounds. Three cationic, three anionic, and two unbounded peroxidases were separated from day‐6 garden cress sprouts. Cationic (GCP1) and anionic (GCP2) peroxidases were purified with molecular masses of 25 and 40 kDa, respectively. The K m values of GCP1 toward H2 O2 and guaiacol were lower than GCP2. The anionic GCP2 exhibited high affinity toward some lignin monomers, sinapyl alcohol, coniferyl alcohol, cinnamic and ferulic acids. Therefore, GCP2 is considered as a lignin peroxidase and contributed in lignin synthesis. The activity of GCP1 and GCP2 was stable at a wide pH range 5.5–8.0 and 6.0–7.5, respectively. Both peroxidases showed the same thermal stability range 20–50°C. GCP2 was more resistant against the effect of metal ions than GCP1. GCP2 showed high ability to remove of phenol and p ‐chlorophenol from effluent compared to GCP1. Practical applications: Generally, garden cress is used as a test plant to conduct biomonitoring of pollution in urban soil on a wide scale because of its simplicity, sensitivity, and cost‐effectiveness. Peroxidase is an important antioxidant enzyme, which elevated when plant subjected to pollution. Recently, we reported that the increase of peroxidase activity was strongly correlated with high phenolic content and antioxidant activity during the germination of garden cress. In the present study, anionic peroxidase GCP2 may play an important role in lignification process and removal of phenol and p ‐chlorophenol from polluted soil/wastewater as well as resisted the harmful effect of heavy metals. Cationic peroxidase GCP1, as a natural scavenger, had high affinity toward H2 O2 coupled to oxidation of some plant phenolic compounds suggesting its role in consuming of excess H2 O2 . Abstract : Cationic (GCP1) and anionic (GCP2) peroxidases were purified from day‐6 sprouts of garden cress. Broad substrate specificity of natural plant phenolic compounds was demonstrated for the purified peroxidases. GCP2 showed a high affinity toward sinapyl and coniferyl alcohols, which contributed in lignin synthesis. GCP2 could be used for removal of phenol and p ‐chlorophenol from polluted soil as well as resisted the harmful effect of heavy metals. GCP1showed a high affinity towards H2 O2 coupled to oxidation of some plant phenolic compounds suggesting its role in consuming of excess H2 O2 .